Emergence of ferroelectricity in Sn-based perovskite semiconductor films by iminazole molecular reconfiguration - Yu Liu; Shuzhang Yang; Lina Hua; Xiaomin Yang; Enlong Li; Jincheng Wen; Yanqiu Wu; Liping Zhu; Yingguo Yang; Yan Zhao; Zhenghua An; Junhao Chu; et al. (Nature Communications)
Abstract Ferroelectric semiconductors have the advantages of switchable polarization ferroelectric field regulation and semiconductor transport characteristics, which are highly promising in ferroelectric transistors and nonvolatile memory. However, it is difficult to prepare a Sn-based perovskite film with both robust ferroelectric and semiconductor properties. Here, by doping with 2-methylbenzimidazole, Sn-based perovskite [93.3 mol% (FA0.86Cs0.14)SnI3 and 6.7 mol% PEA2SnI4] semiconductor films are transformed into ferroelectric semiconductor films, owing to molecular reconfiguration. The reconfigured ferroelectric semiconductors exhibit a high remanent polarization (P r) of 23.2 μC/cm2. The emergence of ferroelectricity can be ascribed to the hydrogen bond enhancement after imidazole molecular doping, and then the spatial symmetry breaks causing the positive and negative charge centers to become non-coincident. Remarkably, the transistors based on perovskite ferroelectric semiconductors have a low subthreshold swing of 67 mv/dec, which further substantiates the superiority of introducing ferroelectricity. This work has developed a method to realize Sn-based ferroelectric semiconductor films for electronic device applications.